Mechanistic insights from animal models of neurofibromatosis type 1 cognitive impairment - Andrew H. Miller; Mary C. Halloran (Disease Models & Mechanisms, 2022)
Neurofibromatosis type 1 (NF1) is an autosomal-dominant neurogenetic disorder caused by mutations in the gene neurofibromin 1 (NF1). NF1 predisposes individuals to a variety of symptoms, including peripheral nerve tumors, brain tumors and cognitive dysfunction. Cognitive deficits can negatively impact patient quality of life, especially the social and academic development of children. The neurofibromin protein influences neural circuits via diverse cellular signaling pathways, including through RAS, cAMP and dopamine signaling. Although animal models have been useful in identifying cellular and molecular mechanisms that regulate NF1-dependent behaviors, translating these discoveries into effective treatments has proven difficult. Clinical trials measuring cognitive outcomes in patients with NF1 have mainly targeted RAS signaling but, unfortunately, resulted in limited success. In this Review, we provide an overview of the structure and function of neurofibromin, and evaluate several cellular and molecular mechanisms underlying neurofibromin-dependent cognitive function, which have recently been delineated in animal models. A better understanding of neurofibromin roles in the development and function of the nervous system will be crucial for identifying new therapeutic targets for the various cognitive domains affected by NF1.